Psychopedagogical Assessment: Systematic Review - Berrío García, Nathaly; Redondo Mendoza, Ciro Ernesto; Mejía Toro, Wilber Arduai (Pensando Psicología, 2020)
Introduction: Psychopedagogical evaluation is a process of data collection, analysis and interpretation, in order to develop explanatory models of the phenomenon of teaching and learning. This evaluation is based on the principle that subjects who are immersed in academic processes have their own unique conditions and their own personal, family and school stories.Methodology: A systematic review of psychopedagogical evaluation was carried out. The search and selection criteria required that the articles be in English and Spanish, be a related to qualitative research andhave been published between 2010 and 2018 in the following databases: EBSCO, Dialnet Plus, ProQuest (Social Sciences and Psychology), Redalyc, Jstor and Scielo.Instruments: To evaluate the methodological quality of the compiled investigations, the “Framework for Assessing Qualitative Evaluations” of the National Center for Social Research was employed, validated by two research experts.Results: 22 studies that met the quality criteria were reviewed. The investigations were mostly developed in Spain. It was found that the issues, commonly associated with psychopedagogical evaluation, are with regards to learning and learning difficulties, classroom evaluation, special needs education, intellectual disability or high intellectual abilities, design of intervention programs, school or educational orientation, inclusive education, diagnosis, cognitive processes or cognitive functions, family participation, school failure and interdisciplinarity. The instruments most used for the collection of information were bibliographic matrices for documentary research, interviews (structured and semi-structured) and some standardized tests.Conclusion: There is a notable growth in scientific and professional interest in psychopedagogical evaluation in the Spanish-speaking world, mainly led by Spain. However, the context and the country’s needs are different compared to those of Latin America. Therefore, it is recommended that professionals in the area perform research to understand psychopedagogy in all its forms and research paradigms, under a Latin American context.
Keywords: learning; teaching; school; psychopedagogical evaluation; systematic guidance and review